Economic Policy Uncertainty and Stock Returns of Africa: A Wavelet Coherence Analysis - Emmanuel Asafo-Adjei; Daniel Agyapong; Samuel Kwaku Agyei; Siaw Frimpong; Reginald Djimatey; Anokye M. Adam (Discrete Dynamics in Nature and Society)
This study explores how global economic policy uncertainty (EPU) shocks comove with stock returns (SR) of eight African countries—Botswana, Ghana, Kenya, Morocco, Namibia, Nigeria, South Africa, and Zambia. The study employed daily data from December 2010 to December 2019 using wavelet coherence analysis. The results showed that global EPU comoves with most of the SR of African markets and was concentrated in the longer term, especially during the period between 2011 and 2019, although not substantially. The findings indicate that short-term investments in African stocks are less susceptible to global economic policy uncertainty. It is recommended that foreign investors could hedge agaist policy uncertainties by investing in stock listed in African Stock exchanges while appropriate country-level policies are deployed to manage long-term effect of EPU.